The Oxford companion to classical literature (Oxford Univ, 1989)
The book remains the lives and works of all the principal authors. Biographical entries present the essential facts and sift conjectural evidence avbout their subjects, while examinations of the major works extend to discussions of the philosophical dialogues and political speeches, and plot summaries of the epic poems and plays. It covers the development of the various literary forms, such as epic, rhetorical writing, comedy, and tragedy, and a full explanation of poetic metre. It is also concerned with putting this literature in the context of its society and history, and consequently there are many articles on the political, social, and artistic achievements of the age; the political climate that produced the great speeches of Demonsthenes and Cicero. Orators, statesmen, and generals stalk the pages. Major battles and conquests, vividly captured by contemporary historians like Thucydides and Caesar in his Commentairies, are her summarized, from the time of Alexander th Great to the fall of Rome. Articles on contemporary social mores and religious beliefs help explain literary references, while the glories of philosophy, science, and art are celebrated from Cynics to Stoics, astronomy to water-clocks, and flute competitions to vase-painting. A helpful series of maps supplements geographical entries on places with important literary connections, and a chronological table provides a comprehensive overview of the main historical and literary events